2013
DOI: 10.1021/ja402480v
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Rich N-Heterocyclic Silylene (NHSi)–Iron Complexes: Synthesis, Structures, and Catalytic Ability of an Isolable Hydridosilylene–Iron Complex

Abstract: The first electron-rich N-heterocyclic silylene (NHSi)-iron(0) complexes are reported. The synthesis of the starting complex is accomplished by reaction of the electron-rich Fe(0) precursor [(dmpe)2Fe(PMe3)] 1 (dmpe =1,2-bis(dimethylphosphino)ethane) with the N-heterocyclic chlorosilylene LSiCl (L = PhC(N(t)Bu)2) 2 to give, via Me3P elimination, the corresponding iron complex [(dmpe)2Fe(←:Si(Cl)L)] 3. Reaction of in situ generated 3 with MeLi afforded [(dmpe)2Fe(←:Si(Me)L)] 4 under salt metathesis reaction, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(108 citation statements)
references
References 71 publications
6
98
1
3
Order By: Relevance
“…To the best of our knowledge, this is the broadest range of substrates for one type of iron-based catalysts. By combined hydrosilylation experiments and density functional theory DFT calculations, Metaänen, Gallego and coworkers [22] investigated the hydrosilylation of a silylene/iron complex that was developed by Driess and coworkers [23]. According to these combined studies, a peripheral mechanism that does not directly involve the metal core was proposed for the hydrosilylation of ketones ( Figure 8).…”
Section: Hmentioning
confidence: 99%
“…To the best of our knowledge, this is the broadest range of substrates for one type of iron-based catalysts. By combined hydrosilylation experiments and density functional theory DFT calculations, Metaänen, Gallego and coworkers [22] investigated the hydrosilylation of a silylene/iron complex that was developed by Driess and coworkers [23]. According to these combined studies, a peripheral mechanism that does not directly involve the metal core was proposed for the hydrosilylation of ketones ( Figure 8).…”
Section: Hmentioning
confidence: 99%
“…In the last few years, new generations of cyclic heavier tetrylene molecules, particularly silylenes and germylenes stabilized by amidinate, β‐diketiminate, and other chelating fragments,4a have allowed a significant advance of the tetrylene–TM chemistry. Among them, the most studied ones have been those derived from amidinates, which form isolatable tetrylene–TM complexes with almost all of the groups of the TM series,9 some of which have already been successfully tested as catalyst precursors for useful reactions,10 such as Sonogashira cross‐couplings,9a ketone hydrosilylations,9b [2+2+2] cycloadditions,9c arene CH borylations,9d and cross‐coupling reactions of aryl halides with organometallic zinc and Grignard reagents 9w…”
Section: Introductionmentioning
confidence: 99%
“…[8] In the last few years, new generations of cyclic heavier tetrylene molecules, particularly silylenes and germylenes stabilized by amidinate, b-diketiminate, and other chelating fragments, [4a] have allowed a significant advance of the tetrylene-TM chemistry. Among them, the most studied ones have been those derived from amidinates, which form isolatable tetrylene-TM complexes with almost all of the groups of the TM series, [9] some of which have already been successfully tested as catalyst precursors for useful reactions, [10] such as Sonogashira cross-couplings, [9a] ketone hydrosilylations, [9b] [2+2+2] cycloadditions, [9c] arene CÀH borylations, [9d] and cross-coupling reactions of aryl halides with organometallic zinc and Grignard reagents. [9w] As part of our work on tetrylene-TM chemistry, [11] we have preliminary communicated that the amidinate-germylene [Ge-(iPr 2 bzam)(HMDS)] (1; iPr 2 bzam = N,N'-bis(isopropyl)benzamidinate), which is equipped with a very bulky hexamethyldisilazane group (HMDS) and armed with just one accessible lone pair of electrons on the Ge atom, can be transformed into a bridging 4-electron-donor k 2 Ge,N-ligand when treated with [Co 2 (CO) 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…22 This study suggested a cooperative relationship between the hydrido-silylene ligand and the Fe(0) center, which mediates the catalytic transformation in a very unique way. We were guided by our earlier work where we demonstrated that the complex [(dmpe) 2 Fe( :Si(H)L)] (27) (dmpe ¼ bis(dimethylphosphino)ethane; L ¼ N,N 0 -di-tertbutyl(phenylamidinato)) is very active in the hydrosilylation of a range of ketones to alcohols in the presence of a suitable hydride source.…”
Section: Albeit In Lower Yieldsmentioning
confidence: 92%